2006
DOI: 10.1017/s1092852900013687
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Amphetamine Salts Extended-Release in the Treatment of Adult ADHD:A Randomized, Controlled Trial

Abstract: Introduction: Attention-deficit/hyperactivity disorder (ADHD) is a serious neurobehavioral disorder of childhood onset that often persists into adolescence and adulthood. Functional impairments, underachievement, and difficult interpersonal relationships illustrate the need for effective treatment of ADHD through adulthood.Method: This prospective, multisite, randomized, double-blind, placebo-controlled, parallel-group, dose-escalation study was conducted to assess the efficacy, safety, and duration of action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
122
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(137 citation statements)
references
References 32 publications
14
122
1
Order By: Relevance
“…This finding is consistent with a previous publication in which a dose response for efficacy was not observed for MAS XR (20, 40, and 60 mg) in adults with ADHD in a 4-week, double-blind, fixed-dose study (Weisler et al, 2006). However, a post hoc analysis of participants with baseline ADHD-RS-IV total scores ≥32 from the same MAS XR study demonstrated that treatment differences in ADHD-RS-IV total score reductions with 60 mg MAS XR were significantly greater than with 20 mg MAS XR (p = .001) and approached significance compared with 40 mg MAS XR (p = .10) (Weisler et al, 2006). Possible contributing factors to the lack of a dose response in this study may be related to the use of forced-dose design, which may not allow for the optimum balance between efficacy and tolerability to be obtained in individual participants, and to the steps used in the titration schedule.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding is consistent with a previous publication in which a dose response for efficacy was not observed for MAS XR (20, 40, and 60 mg) in adults with ADHD in a 4-week, double-blind, fixed-dose study (Weisler et al, 2006). However, a post hoc analysis of participants with baseline ADHD-RS-IV total scores ≥32 from the same MAS XR study demonstrated that treatment differences in ADHD-RS-IV total score reductions with 60 mg MAS XR were significantly greater than with 20 mg MAS XR (p = .001) and approached significance compared with 40 mg MAS XR (p = .10) (Weisler et al, 2006). Possible contributing factors to the lack of a dose response in this study may be related to the use of forced-dose design, which may not allow for the optimum balance between efficacy and tolerability to be obtained in individual participants, and to the steps used in the titration schedule.…”
Section: Discussionsupporting
confidence: 93%
“…Symptom reductions with triplebead MAS were observed as early as Week 1 and continued through 6 weeks of treatment. However, as has previously been observed for MAS XR (Weisler et al, 2006), the key secondary analysis indicated there were no statistically significant differences in the change from baseline ADHD-RS-IV total score at EOS between triple-bead MAS doses. Score reductions on the ADHD-RS-IV subscales followed the same pattern observed for total score, with nominally greater improvement versus placebo observed for all triplebead MAS doses.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Response rates of greater than 75% have been demonstrated with higher doses of both methylphenidate and mixed amphetamine salts. [37][38][39][40] Lisdexamphetamine (Vyvanse ® ; Shire Pharmaceuticals), the once daily prodrug stimulant, was approved by the United States Food and Drug Administration (FDA) for treatment of adult ADHD in 2007. In a study of 420 adults with moderate to severe ADHD by DSM-IV criteria, lisdexamphetamine was superior to placebo in all 3 doses, and patients tolerated it well with minimal side effects.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%